2013
DOI: 10.1186/1471-2407-13-79
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MLH1 and MGMTexpression and promoter methylation with genomic instability in patients with thyroid carcinoma

Abstract: BackgroundGene silencing of the repair genes MLH1 and MGMT was shown to be a mechanism underlying the development of microsatellite instability (MSI), a phenotype frequently associated with various human malignancies. Recently, aberrant methylation of MLH1, MGMT and MSI were shown to be associated with mutations in genes such as BRAF, RAS and IDH1 in colon and brain tumours. Little is known about the methylation status of MLH1 and MGMT in thyroid tumours and its association with MSI and mutational status.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…A study indicated that abnormal methylation of MLH1 was significantly correlated with lymph node metastasis of PTC, suggesting that MLH1 might be a molecular marker of lymph node metastasis in PTC [34]. Another study found that there were abnormal methylation and low expression of MLH1 in thyroid cancer and MLH1 expression is associated with BRAF, IDH1, and NRAS gene mutations [35].…”
Section: Mut-l Homologmentioning
confidence: 99%
“…A study indicated that abnormal methylation of MLH1 was significantly correlated with lymph node metastasis of PTC, suggesting that MLH1 might be a molecular marker of lymph node metastasis in PTC [34]. Another study found that there were abnormal methylation and low expression of MLH1 in thyroid cancer and MLH1 expression is associated with BRAF, IDH1, and NRAS gene mutations [35].…”
Section: Mut-l Homologmentioning
confidence: 99%
“…In addition, Fang et al demonstrated that EGCG in vitro caused a reversal of hypermethylation of retinoic acid receptor beta (RARbeta), p16 (INK4a), O(6)-methylguanine methyltransferase (MGMT), and human mutL homologue 1 (hMLH1) genes in cancer cells with a concurrent effect on the expression of mRNA of these genes [42]. Gene silencing and promoter methylation of mismatch repair (MMR) genes MLH1 and MGMT was shown to be associated to the development of microsatellite instability (MSI) which itself is involved with various human malignancies like cancer [47]. Furthermore, MMR proteins were reported to interact with silencing epigenetic modifiers such as DNMTs when damages exceed the repair capacity [48].…”
Section: Phytochemicals: Modes Of Actionmentioning
confidence: 99%
“…IDH1, isocitrate dehydrogenase 1 [34,35] Produces 2-hydroxyglutarate (2HG), which induces histone-and DNA-hypermethylation through inhibition of epigenetic regulators GNAS, guanine nucleotide stimulatory protein [36] encodes the alpha subunit of the stimulatory G protein. Activating mutation of the alpha subunit of the GNAS gene results in activation of adenylyl cyclase for cell division.…”
Section: Gene Possible Mechanismmentioning
confidence: 99%